Biomechanical Comparison of Three Repair Methods for Proximal Femoral Physeal Fractures in Shear and Tension - Tillson, D. M.; Roush, J. K.; McLaughlin, R. M.; Gaughan, E. M.; DeBowes, R. M. (Veterinary and Comparative Orthopaedics and Traumatology, 1994)
Proximal femoral physeal fractures were created in femora harvested from 64 immature dogs and repaired with one of three repair techniques. Techniques used included a single lag screw placed distal to the trochanter, three divergent pins from below the trochanter, and two screws placed from the articular surface of the femoral head. The re-paired fractures were tested in tension and shear for strength and stiffness. The strength and stiffness were recorded by a hydraulic testing machine and the mode of failure was determined by visual inspection. Fractures repaired with a single lag screw and with the two screws were significantly stronger in tension than those repaired with multiple pins. Significant differences were not found between the repair techniques for shear strength or stiffness in neither tension nor shear. The modes of failure differed between the repair techniques.Three techniques of proximal femoral physeal fracture repair; a single screw from below the greater trochanter, three divergent pins, and two screws placed from the articular sur-face, were tested in tension and shear. Fractures, created on in vitro femora, repaired with a single lag screw and the two screws, were significantly stronger in tension than those repaired with multiple pins. Significant differences were not found between the repair techniques for shear strength or stiffness in neither tension nor shear.
Keywords: Proximal femoral physeal fracture; biomechanical testing; physis; dogs